The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fnut.2021.631934
|View full text |Cite
|
Sign up to set email alerts
|

Not as Bad as I Thought: Consumers' Positive Attitudes Toward Innovative Insect-Based Foods

Abstract: Considering that the demand for food will increase by 70% by 2050, consuming insect-based foods appears as a protein alternative due to their nutritional quality and low environmental impact. However, there is a need to investigate the acceptance of these innovative foods, especially in traditional meat-eating markets, such as in Southern Brazil (land of the Gauchos). The purpose of this manuscript is to analyze consumers' attitudes toward innovative insect-based foods. The methodological procedures were divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
6
2
Order By: Relevance
“…First that no segment is at the time being ready to engage in entomophagy, since the first group which exhibits the highest intention (FCC = 3.80), tends to neither likely nor unlikely engage in entomophagy. This is in contrast with most of the previous segmentation studies, which found at least one segment ready to adopt entomophagy in their diet [ 94 , 123 , 124 ]. Additionally, the findings of this study are in line with almost all previous researchers, who found segments that are reluctant to engage in entomophagy [ 124 , 125 ].…”
Section: Discussioncontrasting
confidence: 86%
“…First that no segment is at the time being ready to engage in entomophagy, since the first group which exhibits the highest intention (FCC = 3.80), tends to neither likely nor unlikely engage in entomophagy. This is in contrast with most of the previous segmentation studies, which found at least one segment ready to adopt entomophagy in their diet [ 94 , 123 , 124 ]. Additionally, the findings of this study are in line with almost all previous researchers, who found segments that are reluctant to engage in entomophagy [ 124 , 125 ].…”
Section: Discussioncontrasting
confidence: 86%
“…Changing dietary habits takes time and effort [37], involving personal [15] and societal views [14]. Consciousness is also a beneficial element [39].…”
Section: Discussionmentioning
confidence: 99%
“…Insect-based food is also influenced by cultural aspects [14]. It is sometimes looked upon as strange or with disgust [15].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…About one-fourth of Nigerian respondents do not accept edible insects as food due to disgust, as insects are perceived as unclean and unsanitary (Ancha et al, 2021). Similarly, insect phobia is the main barrier to consumer acceptance in non-entomophagous countries (Junges et al, 2021;Moruzzo et al, 2021;Sogari et al, 2019c) and in traditional insect-eating countries like China (Hartmann et al, 2015). Hartmann et al (2015) showed that familiarity plays a crucial role in consumer acceptance.…”
Section: Factors Affecting the Consumption Of Edible Insectsmentioning
confidence: 99%